Optimal principles of assessing the quality of graduates in higher education (Eurasian Scientific Herald, 2022)
This article describes the organization of marketing services in higher education institutions and its composition, the selection of marketers with modern marketing knowledge and skills,the financial situation of potential employers, the demand for graduates and the relationship of demand and supply of graduates in a particular specialty